Cluster-based multihop synchronization scheme for femtocell network - Hassan Abdalla Hashim, Aisha; A. Saeed , Rashid; Hasan, Mohammad Kamrul; Islam, Shayla; Khalifa, Othman Omran (IIUM Press, 2012)

(untitled)
Femtocell technology has been drawing considerable attention as a costeffective means of improving cellular coverage and capacity. It is connected to the core network through an IP backhaul and can only use timing protocols such as IEEE1588 or Network Time Protocol (NTP). Furthermore, the femtocell is installed indoor, and cannot use a GPS antenna for time synchronization. High-precision crystal oscillators can solve the timing problem, but they are often too expensive for consumer grade devices. Therefore, femtocell Base Station (fBS) synchronization is one of the principle technical trends in femtocell deployment. Since fBSand macrocell Base Station (mBS) network operates on the same frequency under a licensed spectrum, fBS network can interfere with the macrocell network. In addition, fBSs can also interfere with each other if multiple units are in close proximity. Furthermore, in a flat fBS structured network using IEEE 1588 synchronization algorithm and fBS-fBS synchronization scheme creates offset and frequency error which results inaccurate synchronization. In order to reduce offset and frequency error (skew), this paper proposed a cluster-based multihop synchronization scheme to achieve precise in fBS neighbor nodes. The proposed scheme is able to reduce the offset and skew significantly.